RESTORATIVE JUSTICE: A REVISION OF CRIMINAL PROCEDURE - Walim, Walim (FOCUS: Jurnal of Law, 2025)
The concept of resolving criminal cases through alternative methods has existed since the Dutch colonial era, exemplified by Article 82 of the Indonesian Penal Code (KUHP), which introduced afkoop allowing the dismissal of charges if the offender paid a voluntary fine. Over time, out-of-court settlements evolved, with practices like diversion for children and seponering by the Attorney General in the public interest. These early forms demonstrate the presence of restorative justice in the Indonesian legal system long before the term became widely recognized. This article examines how restorative justice is applied, the principles behind it, and its integration within criminal procedure law. The analysis suggests that restorative justice is particularly effective for minor offenses or cases with limited financial impact, focusing on healing, voluntary participation, and social responsibility. For restorative justice to thrive, the legal system must shift from punishment to recovery, making it essential to the development of a more humane and socially just criminal justice system.